Maslow’s Hierarchy of Needs and Its Relation to Learning and Achievement - Sarah E. Burleson; Andrew C. Thoron (EDIS, 2014)
Learners in courses or training can be preoccupied. They worry about other courses, their home life, friends, extracurricular activities, physiological needs like food and sleep, and the list goes on. When learners are preoccupied with these concerns, learning and achievement are regularly put on the back burner. So how do we get our learners to focus on learning? Instructors can help learners satisfy needs, so the focus can be on content, learning, and achievement. This 3-page fact sheet was written by Sarah E. Burleson and Andrew C. Thoron, and published by the UF Department of Agricultural Education and Communication, April 2014.